#### Answer

57

#### Work Step by Step

When y=3:
Simplify:
2$y^{3}$+$y^{2}$-6
=2$(3)^{3}$+$(3)^{2}$-6
=2(27)+(9)-6
=54+9-6
=63-6
=57

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

57

When y=3:
Simplify:
2$y^{3}$+$y^{2}$-6
=2$(3)^{3}$+$(3)^{2}$-6
=2(27)+(9)-6
=54+9-6
=63-6
=57

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.